Agama dan Identitas Sosial Dalam Praktek Pembelajaran Hadis di Langgar di Kabupaten Malang Jawa Timur - Pradana, Mahatva Yoga; Samsudin; Abror, Indal; Mansur, Muhamamad; Asrowy, Hanan (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2024)
Abstract: This study examines the role of religion in shaping social identity through Hadith learning in the violations of Malang Regency, East Java. This study analyses how the teaching of Hadith in these places of worship affects individuals' perceptions of themselves and their communities. The research methodology involves in-depth interviews with teachers and pilgrims and content analysis of the learning materials used. The results of this study revealed that the practice of Hadith learning in Malang Regency has a significant role in shaping individual social identity. This manifests itself in the influence of religion on social norms, values, and community solidarity. The research also highlights the critical role of teachers in conveying religious messages and how these messages influence individual understanding and identity. This research provides in-depth insights into the complexity of the relationship between religion and social identity in the context of local communities. These findings may contribute to a better understanding of the role of religion in shaping social identity and guide learning efforts, as well as a better understanding of religion in diverse societies. Keywords: Religion, Social Identity, Hadith Learning, Langgar, East Java